2006
DOI: 10.1159/000091620
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Staging Bone Scans in Newly Diagnosed Prostate Cancer

Abstract: Objective: This study aimed to evaluate the role of bone scan as a staging investigation in newly diagnosed untreated prostate cancers. Materials and Methods: Bone scan results in patients with newly diagnosed prostate cancer were reviewed and correlated with clinical stage, prostate-specific antigen (PSA) and Gleason scores from the biopsy specimen. Results: In all, 124 patients fulfilled inclusion criteria with an age range of 51–94 (mean 72.3) years. Pre-biopsy PSA ranged from 2.2 to 5,864 with a median of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
6
1
1
Order By: Relevance
“…Like O'Sullivan et al [12] and Ayyathurai et al [13], but at variance with others [2, 3, 10, 11], we found that PSA level and pathological grade had a higher predictive value in combination. Our overall rate of bony metastases differs from that of a large contemporary study by Briganti et al [14]: 8% vs 2.8%.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Like O'Sullivan et al [12] and Ayyathurai et al [13], but at variance with others [2, 3, 10, 11], we found that PSA level and pathological grade had a higher predictive value in combination. Our overall rate of bony metastases differs from that of a large contemporary study by Briganti et al [14]: 8% vs 2.8%.…”
Section: Discussionsupporting
confidence: 76%
“…Unlike O'Sullivan et al [12] and Ayyathurai et al [13], major Gleason Grade 4 vs 3 made no difference to the rate of bone scan positivity with PSA levels ,20.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A brief mention is made in the RCR guidelines about the importance of primary pattern 4, but it was within the confines of a high‐risk cancer . A conclusion for not doing a BS when the PSA level is <20 ng/mL with Gleason score <8 with cT stage <4, was reached in two UK‐based studies, unless the primary Gleason pattern is 4 . These two studies suggest that PSA level and Gleason score are independent risk factors for BS positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Η μέτρηση της σε συνδυασμό με το PSA αυξάνουν τη διαγνωστική ακρίβεια στο 98% [370]. Παρόλα αυτά, το σπινθηρογράφημα οστών παραμένει η πιο ευαίσθητη μέθοδος αποκάλυψης των οστικών μεταστάσεων και αποτελεί τη μέθοδο εκλογής όταν το PSA είναι μεγαλύτερο από 20 ng/ml [371][372][373][374]. Τέλος, για τη διαπίστωση μεταστάσεων σε άλλα συμπαγή όργανα, η αξονική και η μαγνητική τομογραφία, το υπερηχογράφημα κοιλίας και η κλινική εξέταση αποτελούν τις μεθόδους εκλογής [375].…”
Section: ποια είναι η κλινική σημασία των κλασμάτων του Psa;unclassified